SKRIPSI : Analisis Frekuensi Sweep Sistem Pendinginan Konveksi Paksa Menggunakan Jet Sintetik Nozzle X dan Z - Ahmad Fikri Khair Ashal, (2020)
Synthetic jet was a solution that could be used as a cooled device in more modern electronics. There were many variations that could be used in synthetic jet research such as the nozzle shape, frequency, and actuator used. These research were conducted to variation the sweep frequency wave and the shape of nozzle used the alphabet letters x and z. Selection of frequency sweep and the shape of the nozzle was expected to provided a better heat transfered effect as an innovation, if were compared to natural covection cooled. These research was conducted used speakers as actuator on these synthetic jet. The results of these experimental research showed synthetic jet with variations in sweep frequency with x shape nozzle capable of produced cooled, with a good final temperature at frequency of 120hz - 420hz and z shape nozzle is capable of produced the best final temperature at a frequency of 80hz - 380hz if were compared to natural convection cooled. While in the results of fluid flow simulations used cfd in these studied founed the highest vorticity, turbulence, and velocity value on fluid flow was produced generated by the x-shape nozzle at a frequency of 120hz - 420hz. While the highest velocity value on the fluid was produced by the z-shape nozzle for all frequency used. The result of these research had showed that synthetic jets used variations in sweep frequency using x and z form nozzles could increase heat transfer if was compared to natural convection cooling.